Factors influencing student mobility: a comparative European study. Issue 12 (2nd December 2021) - Perez-Encinas, Adriana; Rodriguez-Pomeda, Jesus; de Wit, Hans
ABSTRACT: A range of different factors drive student decision-making with respect to studying abroad, they are called push and pull factors. They influence in the (non)-mobility experience of students. This paper focuses on the international student experience, predominantly focusing on: credit-degree mobility and bachelor – master students. The aim of this paper is to identify enablers and obstacles within the process of going abroad according to service provision along the international student lifecycle. By applying an innovative method – Latent Dirichlet Allocation (LDA) – to employ new techniques when looking for hidden structures in large numbers of texts (73, 715 reviews from international students), we conclude that they exist significant differences between degree and credit mobility students, and not when comparing bachelor and master students. As a result, both groups of students place importance on three main aspects during their international experience: offerings of the city, social life and academics.